help, please.. . Let f(x) = 2x2 – 2x + 7 and g(x) = x2 + 9x – 6. Find f(x) – g(x).. . x2 – 11x + 13. . x2 – 11x + 1. . x2 + 7x +
1. . x2 + 7x + 13
1 answer:
F(x) = 2x² - 2x + 7
g(x) = x² + 9x - 6
f(x) - g(x) = 2x² - 2x + 7 - (x² + 9x - 6)
= 2x² - 2x + 7 - x² - 9x + 6
= 2x² - x² - 2x - 9x + 7 + 6
= x² - 11x + 13
The 1st option.
You might be interested in
Answer:
Isosceles triangle
Step-by-step explanation:
A triangle that contains 2 equal sides but one side different
Answer:
56
Step-by-step explanation:
11*4=44
6*2=12
44+12=56
Answer:
Step-by-step explanation:
Distribute (2h − 3k)(h + 5k).
2h^2 + 10hk - 3hk - 15k^2
2h^2 + 7hk 15k^2
Answer:
g(x)=|x|
Step-by-step explanation:
Answer:
2010
Step-by-step explanation: